Problem Based Learning menggunakan Kompetensi 4C: Implementasi pada Pembelajaran Ekonomi - Reni Widia; Syamwil Syamwil (Jurnal Ecogen, 2023)
This study aims to determine the effect of the 4C (Collaboration, Critical Thinking, Creativity, and Communication) problem-based learning model on the results of economic learning in year XI IPS MAN 2 Kota Padang. The quasi-experimental population of the study consists of students in the all-year XI IPS MAN 2 Kota Padang community. Technique used was purposeful sampling. The trial used a nonequivalent control group design.  Prior to using the t-test statistic for hypothesis testing, the normality test and homogeneity test, both having a sig. 5%, were employed as analytical tests. The results of the study showed that the average post-test score for the experimental class, which was 84.50, was higher than the average score for the control class, which was 77.10, according to the study's findings. According to the t-test, tcount = 5,4 and tcount is greater than ttabel.  H0 is disapproved whereas this Ha is accepted. Consequently, it was determined that the Problem-Based Learning model had an impact using 4C (Collaboration, Critical Thinking, Creativity, Communication) on student learning outcomes than a conventional model.